Sex Estimation Using Subpubic Angle From Reconstructed Three-dimensional Computed Tomography Pelvic Model In A Contemporary Malaysian Population - Siti Hanum Mohd Ali; Normaliza Omar; Mohamed Swarhib Shafie; Nik Azuan Nik Ismail; Helmi Hadi; Faridah Mohd Nor (Korean Association of Anatomists, 2024)
Volume:53 (Pages: 27-35)